A new genus and species of arboreal toad with phytotelmonous larvae, from the Andaman Islands, India (Lissamphibia, Anura, Bufonidae) - Chandramouli, S.R.; Vasudevan, K.; Harikrishnan, S.; Dutta, S.; Jegath, Janani S.; Sharma, Richa; Das, I.; Aggarwal, Ramesh K. (Pensoft Publishers, 2016)
A new bufonid amphibian, belonging to a new monotypic genus, is described from the Andaman Islands, in the Bay of Bengal, Republic of India, based on unique external morphological and skeletal characters which are compared with those of known Oriental and other relevant bufonid genera. Blythophryne gen. n. is distinguished from other bufonid genera by its small adult size (mean SVL 24.02 mm), the presence of six presacral vertebrae, an absence of coccygeal expansions, presence of an elongated pair of parotoid glands, expanded discs at digit tips and phytotelmonous tadpoles that lack oral denticles. The taxonomic and phylogenetic position of the new taxon (that we named as Blythophryne beryet gen. et sp. n.) was ascertained by comparing its 12S and 16S partial genes with those of Oriental and other relevant bufonid lineages. Resulting molecular phylogeny supports the erection of a novel monotypic genus for this lineage from the Andaman Islands of India.